Professionalization of social work in Russia: challenges for education system. Issue 3 (3rd April 2019) - Smirnova, Anna; Poluektova, Nina
ABSTRACT: The article presents the ongoing professionalization of social work in Russia, with focus on the challenge of integrating Professional Standards into the current educational system. To understand the complexity of training social work professionals, we analyze the historical roots of the profession in Russia and the current trends that shape professional identity, such as the influence of neoliberal policy on social work. The traditions of the Russian higher education system, which are currently being challenged by the need to modify teaching programs to accommodate modern practical demands, are also discussed. Under pressure from employers to provide graduates who are 'job ready', Russian universities have to prove that their graduates have the appropriate skills to meet the requirements of newly formed Professional Standards. In fact, integrating the labor market with the education system by coordinating the narrow specializations of Professional Standards with the wide competences of earlier formulated Educational Standards is a complex issue. Ultimately, we contend that social work education in the Russian context should be built on the basis of harmonizing traditional academic education with new practical experiences, and give the example of how St Petersburg State University is seeking to transform its educational strategy to meet new challenges.